Assessment of Turbulent Mixing Associated With Eddy‐Wave Coupling Based on Autonomous Observations From the Arctic Canada Basin. Issue 9 (13th September 2022) - Son, E. Y.; Kawaguchi, Y.; Cole, S. T.; Toole, J. M.; Ha, H. K.
Abstract: Interaction between mesoscale eddies and near‐inertial internal waves can contribute to enhanced turbulence mixing but quantitative knowledge from in situ observations is still lacking. This study reveals how eddy/near‐inertial wave interactions (ENIs) can affect the variability of turbulent mixing in the ice‐covered Canada Basin of the Arctic Ocean. We use data from five Ice‐Tethered Profiler with Velocity (ITP‐V) systems that autonomously obtained vertical profiles of horizontal velocity as well as temperature and salinity, which enabled quantification of ENI‐caused turbulent mixing using a fine‐scale parameterization. From the ITP‐V observations in 2013–2015, 67 anticyclones were detected, of which 90% had a deep core at 150–250 m depth. The remaining eddies had a shallow core, typically embedded in the Pacific Summer Water (PSW). Just over one third of the eddies showed evidence of ENI with enhanced near‐inertial internal wave amplitude (NIW) near the eddy cores. For these ENI cases, the parameterized turbulence dissipation rate was O (10 −10 –10 −8  W kg −1 ), the larger estimates being several orders of magnitude greater than the background level. For the deep eddies, the ENI process can largely be accounted for by the classical theory, NIWs are trapped inside the negative relative vorticity core of anticyclones. For one shallow eddy, the NIW signal was greatest below the core. We postulate that a vertically elongated system of NIWs cannot be constrained vertically within such small‐cored eddies. It is also interpreted that the wave enhancement below the core was supported by the isopycnal slope near the PSW through its geostrophic shear. Plain Language Summary: Two ocean phenomena, eddies and internal waves, are known to interact and contribute to hotspots of strong mixing in the upper ocean. We analyze extensive observations of the interaction of eddies and internal waves in the ice‐covered Arctic Canada Basin using data from several autonomous instruments: the Ice‐Tethered Profiler with Velocity (ITP‐V). The ITP‐V repeatedly measures vertical profiles of ocean temperature, salinity, and currents at 1 m vertical resolution. During 2013–2015, ITP‐Vs encountered 67 individual eddies with core depths ranging between 40 and 250 m. Of these, 90% were found at depths of 150–250 m, while the rest were shallow features. Approximately one third of the observed eddies exhibited internal waves with enhanced amplitudes near the eddy core depths that are inferred to support intensified mixing. For the deep eddies, the amplified waves were mostly observed within the eddies, consistent with previous studies. For one shallow eddy, enhanced wave signals were found below something that has not been previously reported. For this case, we deduced that the sloping stratification associated with the eddy azimuthal flow modified the propagation of waves and resulting in the enhanced mixing on the underside of the eddy. Key Points: High‐resolution autonomous observations of hydrography and currents were conducted in pack ice regions of the Canada Basin, Arctic Ocean Interaction between anticyclonic mesoscale eddies and near‐inertial internal waves enhanced turbulent mixing roughly by factor of two A shallow eddy showed significant wave enhancement below its core resulting from combination of negative vorticity and slanted isopycnals